Transplacental transfer of cefuroxime in uncomplicated pregnancies and those complicated by hydrops or changes in amniotic fluid volume. Issue 1 (January 1993) - Holt, D E; Fisk, N M; Spencer, J A; de Louvois, J; Hurley, R; Harvey, D
Abstract : The transplacental transfer of cefuroxime was determined at antenatal fetal blood sampling in a cross sectional study of 78 patients between 15-35 weeks' gestation, 8-138 minutes after a maternal intravenous dose of 750 mg. Mean serum cefuroxime concentration, measured by high performance liquid chromatography, was 7.4 (95% confidence interval (CI) 6.8 to 8.1) mg/l in control fetuses; concentrations in hydropic fetuses were similar (6.2 mg/l, CI 4.7 to 7.7) but in fetuses with oligohydramnios they were significantly lower, (4.9 mg/l, CI 3.6 to 6.2). Antibiotic concentration did not correlate with gestational age and remained unchanged by transfusion of packed red cells. We conclude that (i) fetal serum concentrations of cefuroxime obtained after a maternal dose of 750 mg are only adequate for prophylaxis against organisms with a minimum inhibitory concentration of < 4 mg/l and (ii) transplacental passage of cefuroxime is significantly reduced in the presence of oligohydramnios.